Determinants of Return on Assets in Banking Companies Listed on the Indonesia Stock Exchange - Dita Ayu Nurani; Farah Margaretha Leon (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effects of Non-Performing Loans (NPL), Shareholder Equity Ratio (SER), Solvency Ratio (SVR), and Liquidity Ratio (LR) as independent variables on Return on Assets (ROA) among banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative research approach was employed using secondary data obtained from the annual reports of the selected companies. The study sample comprised 33 banking companies, resulting in a total of 165 observations. Data were analyzed using panel data regression with the Random Effect Model (REM), processed through EViews version 13.0. The findings indicate that NPL and SVR have a negative and statistically significant effect on ROA, while LR has a positive and statistically significant effect on ROA. In contrast, SER does not exhibit a statistically significant effect on ROA.